Sinergi Model Sewa Guna Usaha Dengan Model Pembiayaan (Financing) Pada Sektor Pariwisata (Studi Kasus Di Kabupaten Lombok Utara) - Susanto, Hery; Putra, I Nyoman Nugraha Ardana; Pituringsih, Endar (Sekolah Tinggi Ilmu Ekonomi AMM, 2024)
North Lombok District (KLU) has great potential in the tourism sector, but faces economic challenges, including the tendency of communities to sell land to meet short-term needs. This study aims to develop a leasing-based financing model to support the sustainability of the tourism sector in KLU. This model integrates the Community-Based Tourism (CBT) approach, which involves local communities in management and decision-making. Research data were obtained through in-depth interviews with landowners and other stakeholders, using thematic analysis methods. The results show that leasing can be an alternative financing solution, enabling productive land use without loss of ownership. Synergy between the community, government and private sector was found to be key to the success of this model. This research contributes to the literature by offering an innovative approach that supports economic and social sustainability in rural tourism areas